Budget Deficits and Public Borrowing Instruments in an Islamic Economic System - Monzer Kahf (International Institute of Islamic Thought, 1994)
In this rapidly changing world, several countries and political movements, especially in the Middle East, are calling for the establishment of an Islamic economic system. This paper seeks to explain the area of public borrowing in such a system and to explore its use in today’s world In the literatwe, the term “budget deficit” denotes the gap between public revenue and expenditures. Revenues normally come from taxation and public property, while expenditures may cover development projects and cumnt governmental expenses. In general, such a deficit is bridged by increasing revenues, reducing expenditures, internal borrowing (i.e., from the public commercial banks or the central bank), and by external borrowing. In the past, governments used to borrow from their rich citizens only to meet the financial needs associated with wars and natural calamities. Today, however, public bornwing has become a major feature of contemporary economies in both developed and developing countries. This paper cosists of four sections: the principles of financing in Islam, the Islamic point of view on the provision of public goods, various instruments for public resource mobilization that can be developed on the basis of Islamic principles of financing, and a conclusion. The Principles of Financing There are several recorded cases of public borrowing during the time of the ptophet, as well as othets by the ‘AbWd and the Ottoman governments (Siddiqui 1992). This practice has petsisted into the modem era, as evidenced by Egypt and the Ottoman Empire during the middle of the ...